Musica e Psicologia allo specchio. Lo spartito dell'empatia (Materiali di Estetica. Terza serie, 2025)
When music and psychology meet, strange magic happens: one mirrors the other. A different path, therefore, opens up to the musician, when the relational aspect of sound is rediscovered. Only sensorimotor empathy, in fact, can transform anxiety into an opportunity for connection, using mirror neurons. It is necessary, however, to recognize the evolutionary function of anxiety, as an ally of music and not as an enemy to be avoided or controlled. Too many perfect musical performances, without soul and without human warmth. So, it is urgent to bring the empathic relationship back into musical education, as well as into concert, placing the intimate exchange between composer, performer and audience at the center. Only in this way, anxiety will transform into authentic sharing, where the listener, in an active way, will be able to mirror what the composer and performer wish to communicate, becoming co-protagonist of the same life multisensory experience.